Conceptual Interaction Of Banditry And Access To Land As Emergent Trends Of Inter-Ethnic Conflict In Nigeria - Cletus O. Obasi, Lilian Chinelo Nwokafor,Olisa Anthony Enweonwu (International Journal of Advanced Science and Technology, 2020)
The Paper Explains Banditry As A Social Phenomenon That Supplants Local Cultures And Ideologies. Banditry Creates Terror, Gruesome Killings And Dispossesses Communities Of Their Land And Properties. Thousands Of People Have Lost Their Lives Across The Most Populous Black Nation Entity Called Nigeria By Banditry Activities; Which In Most Cases Could Be Nationals Or Foreign Nationals With Trans-Border Criminalities Tendency Forcing Millions Of People To Flee Their Ancestral Homes And Embarked On Journey Of No Return. The Question That Is On The Lips Of People Is ‘What Is The Government Doing About It?’ Factors Such As Unemployment, Bad Governance, Poverty, Marginalization And Social Imbalance, Play A Key Role In Producing Bandits And Terrorists. Banditry Multiplier Effects Include Food Insecurity, Unemployment, Poverty And Marginalization Fuelling InterEthnic Crisis In Nigeria. The Crises Have Also Scared Away Foreign Investments And As A Result, Inflation Has Increased. This Paper Aims To Probe The Reasons For Banditry And Its Socio-Economic Effects On The Life Of The People. This Paper Adopts Alternative Dispute Resolution (Adr) As A Panacea For Banditry And Its Resultant Ethnic Conflicts.